S.M.A.R.T. Circle Projects - Liu, Andy (Springer Texts in Education,, 2018)
This book describes projects in a Mathematical "Circle," i.e., an organization that discovers and nurtures young mathematical talents through meaningful extra-curricular activities. This is the second volume in a trilogy describing in particular the S.M.A.R.T. Circle project, which was founded in Edmonton, Canada in 1981. The acronym S.M.A.R.T. stands for Saturday Mathematical Activities, Recreations & Tutorials. This book, Volume II, is based on the papers published in scientific and education journals by the Circle members while they were still in junior high school (some still in elementary school). In essence, it explains the purpose of the Circle. Volume I describes how to run a Circle, and Volume III explains what actually takes place in the Circle. All three volumes provide a wealth of resources (mathematical problems, quizzes and games, together with their solutions). The books will be of interest to self-motivated students who want to co nduct independent research, teachers who work with these students, and teachers who are currently running or planning to run Mathematical Circles of their own.